A survey of library skills and computer literacy of new students entering the University Of Malaya: 1996/97 - Chall, D.K.; Lim, S.H. (University of Malaya Library, 1997)
Report on the findings of a survey of the library skills and computer literacy of 2058 students entering the University of Malaya in the 1996/97 academic session. Although most students were familiar with libraries, they lacked searching skills associated with electronic retrieval of inforation particularly keyword searching. Almost 60% of the students said they knew how to use a computer. However, their computer skills were largely confined to word processing. Very few were familiar with accessing the Internet, using multimedia, searching CD-ROM and online databases and using a computerised catalogue. It was also found that about half of them were able to differentiate between a book citation and a journal article citation.